Maine and Offshore Wind Development: Using the Coastal Zone Management Act and Marine Spatial Planning to Influence Projects in Federal Waters - Morrissey, Mary (Maine Policy Review, 2022)
Federal and state governments have developed ambitious goals for offshore wind projects. While Maine wants to take part in this trend, it has passed a moratorium on offshore wind projects in state waters. Considering this ban, pressure to develop offshore wind energy, and potential impacts of such projects on local ecology and habitats, Maine needs to develops a strong voice in offshore wind projects in federal waters. This article looks to Rhode Island to show how Maine can participate in decisions about offshore wind development and compares Maine’s current offshore wind efforts and potential for marine spatial planning to Rhode Island’s. The article also proposes short- and long-term actions to guide Maine’s development of the offshore wind industry in federal waters.